Soil quality ranking of a small sample size using AHP - KUMAR, NIRMAL; SINGH, S. K.; MISHRA, V. N.; REDDY, G.P. OBI; BAJPAI, R. K. (Journal of Soil and Water Conservation, 2020)
Soil quality ranking of a small sample size have been attempted. Principal component analysis (PCA) - the most popular approach to define an appropriate minimum data set (MDS) and their weights for integrating these into Soil Quality Index (SQI) - will easily produce errors of inference in these conditions. Our objective was to develop a soil quality assessment protocol for cotton growing soils of Hinganghat, a major cotton growing tehsil of Wardha district. A small sample size of eleven soil series reported to occur in the tehsil were selected. Soil depth, available water capacity (AWC), cation exchange capacity (CEC), and organic matter (OC) were selected as MDS based on experts’ opinion (EO). For defining weights of the indicators, Analytical Hierarchical Process (AHP) was used. AHP is widely used multicriteria decision method which determines the weight based on pair-wise comparisons of parameters according to relative importance. The AHP approach was found to be handy in calculating SQI especially, in case of small sample size.